(Mis)understanding the Hijab: the spirit and strength of Somali girls. Issue 1 (2nd January 2020) - Leet-Otley, Jill
ABSTRACT: Somali girls who veil are often misrepresented as being oppressed by a patriarchal culture. Research gathered from a critical ethnographic study with sixth grade Somali girls sheds light on their understanding of the hijab and their experiences with anti-Muslim discrimination. Findings reveal that the hijab provided a source of strength from which they embraced, contested, and negotiated sometimes-competing American and Somali gender norms. Wearing hijab also functioned as an act of resistance to the overt sexualization and Islamophobia they experienced in the mainstream culture. Furthermore, wearing hijab may be advantageous because immigrants who maintain strong ethnic identities and close connections to their home culture often achieve better educational outcomes than immigrants who rapidly assimilate.